7 - Are Ghanaian Diaspora Middle Class? Linking Middle Class to Political Participation and Stability in Ghana - Hamidu, Jamilla (Africa Development, 2021)
Ghana, like many African countries, has had its fair share of political instability in the aftermath of independence. In the late 1960s, 1970s and 1980s, the country witnessed some political turbulence, marked especially by a long period of dictatorial military rule. However, since the return to constitutional rule in 1992, Ghana has emerged as one of the most stable countries in the West African sub-region and has become a beacon of democracy for other African countries to emulate. This political stability has been largely attributed to the positive role of the educated middle class from the diaspora. This article provides a case study of the Ghanaian diaspora, as middle class and the role they have played and continue to play in maintaining Ghana’s political stability. A field work was conducted between February 2012 and May 2013 to ascertain what constitutes Ghana’s middle class and establish their link to political stability in Ghana. The sample consisted of 52 respondents in Accra who were interviewed using a semi-structured questionnaire. What constitutes the Ghanaian middle class? How do they organise themselves politically? Are they truly the vanguard of political stability in Ghana? If so, how have they accomplished this? These are some of the questions the article will provide answers to.